Microstrip patch antenna review on various parameters, methods and its applications - Kannadhasan Suriyan; Nagarajan Ramaingam (International Journal of Informatics and Communication Technology (IJ-ICT), 2023)
The implementations of the microstrip patch antenna for wireless local area network (WLAN) and worldwide interoperability for microwave access (WiMAX) are analyzed in the literature in this research. Dual or multiband antenna has played a significant part in meeting the expectations of wireless service in this quickly developing world of wireless communication. Basically, a transitory guide, an antenna is a device that emits or absorbs radio waves. Numerous benefits exist for microstrip patch antennas, including affordability, portability, simplicity of construction, and compatibility with integrated circuits. This has several important uses in the military, radar, mobile communications, global positioning system (GPS), remote sensing, and more. In mobile devices like portable computers and smartphones, WLAN and WiMAX are often used.